The impairment of plasma kallikrein action on homeostasis by kallikrein inhibitor comprising RGD sequence established a novel target in antithrombotic therapies. (November 2022) - Medina, A.F.; Salu, B.R.; de Brito, M.V.; Bonturi, C.R.; Meneghetti, M.C.Z.; Maffei, F.H.A.; Oliva, M.L.V.
Abstract: Coagulation contact pathway inhibitors have aroused interest in the treatment and prevention of thrombosis due to their lower hemorrhagic effects. We investigate the recombinant kallikrein inhibitor (rBbKIm) containing the RGD/RGE motif and its related peptides in arterial thrombosis models. rBbKIm prolonged activated partial thromboplastin time by 3.5 (8.6 µM) and 4.1 times (17.2 µM), and extended the arterial occlusion time in a dose-dependent manner: 2.0 mg/kg (48.83 ± 15.87 min), 4.0 mg/kg (73.06 ± 21.38 min) and 8.0 mg/kg (94.13 ± 11.25 min) compared with control (0.15 M NaCl, 29.70 ± 7.14 min). Similar results were obtained with the RGD-peptide, 2.5 mg/kg (62.85 ± 18.53 min) and 5.0 mg/kg (89.50 ± 8.63 min). Thrombus sizes were decreased in the rBbKIm, RGD-peptide, and fondaparinux (0.7 mg/kg) treated groups, due to reduced adhesion of platelet to the endothelium. ADP-induced platelet aggregation ex vivo was inhibited by both rBbKIm (4.0 mg/kg, 75 %) and the RGD-peptide (5.0 mg/kg, 56 %), and they did not modify the bleeding time in contrast to fondaparinux. rBbKIm and RGD-related-peptide delayed the artery occlusion and reduced the thrombus size without any modification of the bleeding time, thereby impairing the aggregation and/or adhesion of platelets, making them useful for thrombosis therapy. Graphical Abstract: ga1 Highlights: PKa blockade may be a new target in antithrombotic therapies. The RGD sequence in PKa inhibitor is important for its specific antithrombotic action. Plasma kallikrein is a target to be explored in antithrombotic therapies. Inhibitors containing RGD interfere with platelet aggregation, preventing thrombosis